Penerapan DPE Framework dalam Perancangan Serious Game bagi Pengidap Kebutaan Nada - M. Rizkiyan Zaka Riawan; Wibisono Sukmo Wardhono; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Tone deafness, wich known as congesti amusia, is kind of disability to sing the note correctly. Tone deafness can be detected through tests that apply the montreal battery method, used to determine a person's ability to compare the level of tone and recognize patterns of ups and downs. Based on the problems above, then designed serious game that aims to therapy for people with tone deafness. The design of this serious game is implementing DPE (Design, Play, Experience) framework, that divides designing process into multiple layers. These layers include: learning layer, layer storytelling, gameplay layer, user experience layer, and the technology layer. The tests wich conducted in this serious game is play test and tone deafness competency test. In play test, questionnaires will be used as a testing tool, containing questions related to the player's interest towards content and idea of this game. On the tone deafness competency test, participants ability to descriminate tones will be analysed, which is represented by the score of the tone deafness test. From the results of these tests, can be concluded that serious games are designed in compliance with the objectives learning as well as the excitement factor wich is the essence of a game.